Information flows within financial conglomerates: Evidence from the banks–mutual funds relation - Massa, Massimo; Rehman, Zahid (Journal of Financial Economics, 2008)
We study how information flows within financial conglomerates by analyzing the relations between mutual funds and banks that belong to the same financial group. We investigate the effect that the lending behavior of affiliated banks has on the portfolio choice of the mutual funds that are part of the same group. We show that funds (fund families) increase their stakes in the firms that borrow from their affiliated banks in the period following the deal by far greater amounts than other unaffiliated funds (fund families). We provide evidence that this strategy is information-driven. The performance of the positions of affiliated funds in the stocks of borrowing firms exceeds that of their other positions in nonborrowing stocks located in the same industry as well as that of other stocks having similar characteristics by up to 1.6% per month. Funds increase (decrease) their stock holdings in those borrowing stocks that subsequently provide positive (negative) abnormal returns, suggesting that they exploit privileged inside information not available to other market participants. This behavior is prevalent largely in funds located in close geographic proximity to their lending banks. Furthermore, it is exhibited mostly by young, small, and poorly performing fund families. Our evidence points to information flows within conglomerates through informal channels such as personal acquaintances.